2011
DOI: 10.1149/1.3556609
|View full text |Cite
|
Sign up to set email alerts
|

The Phase Change Effect of Oxygen-Incorporation in GeSbTe Films

Abstract: Reflectivity changes in oxygen-incorporated Ge2Sb2Te5 (GST) films were investigated via a laser-induced crystallization process. The crystallization process showed that the phase change speed and the laser power required for crystallization become faster and larger in GST films with a characteristic quantity of oxygen. We confirmed that a dominant grain growth mode during the laser crystallization is a major determinant for the speed of phase change in GST films with a characteristic quantity of oxygen. JMA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…are the values of resistance in the fully amorphous and crystalline phases. The JMA kinetics is an equation for kinetics in the phase transition mechanism, generally expressed as shown in Equation (2) [21,22]. xfalse(tfalse)=1expfalse[false(ktfalse)nfalse] where n is the Avrami coefficient and k is the effective rate constant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…are the values of resistance in the fully amorphous and crystalline phases. The JMA kinetics is an equation for kinetics in the phase transition mechanism, generally expressed as shown in Equation (2) [21,22]. xfalse(tfalse)=1expfalse[false(ktfalse)nfalse] where n is the Avrami coefficient and k is the effective rate constant.…”
Section: Resultsmentioning
confidence: 99%
“…xfalse(tfalse)=1expfalse[false(ktfalse)nfalse] where n is the Avrami coefficient and k is the effective rate constant. Equation (2) can be modified to deal with the R–t curve, as follows: [21,22,23] lnfalse[lnfalse[11xfalse(tfalse)false]false]=nlnt+nlnk…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the JMA plot characterizes the isothermal crystallization on the minute time scale, it is also possible to subtract the Avrami coefficient, n, from the nanosecond time scale, as we previously reported. 26 Fig. 3(e)-(h) show JMA plots on the nanosecond time scale at a laser power of 40 mW.…”
Section: ) and (I) †mentioning
confidence: 99%
“…By comparing our previous results on oxygen-incorporated GST lms with the results of this study, BN-incorporated GST lms were found to have better phase change speed and stability. 26,28 The JMA plot for oxygen-doped GST indicates that, for the generation of nucleation sites, it is required to wait for about 30 ns. However, in BN-incorporated GST, there is no incubation period for nucleation sites because BN molecules already act as nucleation sites.…”
Section: ) and (I) †mentioning
confidence: 99%